2008
DOI: 10.3201/eid1410.080703
|View full text |Cite
|
Sign up to set email alerts
|

New Hosts for Equine Herpesvirus 9

Abstract: Equine herpesvirus 9 was detected in a polar bear with progressive encephalitis; the source was traced to 2 members of a potential equid reservoir species, Grevy's zebras. The virus was also found in an aborted Persian onager. Thus, the natural host range is extended to 6 species in 3 mammalian orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
62
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 10 publications
0
62
0
Order By: Relevance
“…Recently, it has been reported that the host range of EHV-9 has expanded to include Grevy's zebras (Equus grevysi) and polar bears (Ursus maritimus), 7,31 as well as a giraffe (Giraffa camelopardalis reticulata).…”
mentioning
confidence: 99%
“…Recently, it has been reported that the host range of EHV-9 has expanded to include Grevy's zebras (Equus grevysi) and polar bears (Ursus maritimus), 7,31 as well as a giraffe (Giraffa camelopardalis reticulata).…”
mentioning
confidence: 99%
“…The virus was identified as EHV-1 based on DNA fingerprinting and serological analyses (Montali et al, 1985). PCR and DNA sequencing analyses of the DNA polymerase showed that the zebras and the onager had an EHV-9 strain identical to that found in the polar bear (Schrenzel et al, 2008). …”
Section: Meningoencephalitis In a Polar Bearmentioning
confidence: 76%
“…A 12-year-old female polar bear (Ursus maritimus) developed a sudden onset of neurological symptoms in 2007 (Schrenzel et al, 2008;Donovan et al, 2009). Nonsuppurative pleocytosis of cerebrospinal fluid was observed.…”
Section: Meningoencephalitis In a Polar Bearmentioning
confidence: 99%
See 2 more Smart Citations